Engineering new strategies to improve pharmacokinetics of therapeutic proteins - Cantante, Cátia Sofia de Carvalho, 1982- (2014)
Tese de doutoramento, Farmácia (Biotecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2014